2011
DOI: 10.2225/vol14-issue2-fulltext-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermentation temperature on the composition of beer volatile compounds, organoleptic quality and spent yeast density

Abstract: Production of good quality beer is dependent largely on the fermentation temperature and yeast strains employed during the brewing process, among others. In this study, effects of fermentation temperatures and yeast strain type on beer quality and spent yeast density produced after wort fermentation by two commercial yeast strains were investigated. Beer samples were assessed for colour, clarity and foam head stability using standard methods, whilst the compositions and concentration of Beer Volatile Compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…The ethyl acetate content exceeds the sensory sensation threshold to only a moderate extent. Since any higher concentration of ethyl acetate is undesirable in beer, the results are in agreement with quality requirements for the beverage [22]- [24].…”
Section: The Formation Of Esters and Alcohols As Part Of The Main supporting
confidence: 82%
See 1 more Smart Citation
“…The ethyl acetate content exceeds the sensory sensation threshold to only a moderate extent. Since any higher concentration of ethyl acetate is undesirable in beer, the results are in agreement with quality requirements for the beverage [22]- [24].…”
Section: The Formation Of Esters and Alcohols As Part Of The Main supporting
confidence: 82%
“…The decrease in the content of volatiles in the beer as part of fermentation is not caused by reduced formation. Rather, displacing by carbon dioxide is the reason for the reducing level [20], [22]. With the beer becoming saturated after three weeks, the extent of the loss is not so considerable and the level of volatiles gradually increases (see Fig.…”
Section: The Formation Of Esters and Alcohols As Part Of The Main mentioning
confidence: 99%
“…Olaniran et al . also examined the effect of the different fermentation temperatures on the viability of the yeast population. In their study, the least viable population was observed at a fermentation temperature of 30°C compared with the much lower temperature of 18°C.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous fermentation parameters affect the synthesis of higher alcohols and esters during lager yeast brewing, such as wort gravity, wort composition, temperature, pressure, oxygen and pitching rate (16)(17)(18)(19)(20)(21)(22)(23). A factor of significant importance for flavour production of beer is wort composition.…”
Section: Introductionmentioning
confidence: 99%